Production and Optimization of Oleic Acid Ethyl Ester Synthesis Using Lipase From Rice Bran (Oryza sativa L.) and Germinated Jatropha Seeds (Jatropha curcas L.) by Response Surface Methodology - Indro Prastowo; Chusnul Hidayat; Pramudji Hastuti (Indonesian Journal of Biotechnology, 2012)
Recently, the fatty acid ethyl ester has been synthesized in place of fatty acid methyl ester since ethanol has been more renewable. In this research, oleic acid ethyl ester (OAEE) was synthesized using germinated jatropha seeds (Jatropha curcas.L) and rice bran (Oryza sativa) as source of lipase. The objective of the research was to optimize the synthesis conditions using Response Surface Methodology. Factors, such as crude enzyme concentration, molar ratio of oleic acid to ethanol, and the reaction time, were evaluated. The results show that lipase from germinated jatropha seeds had the hydrolitic and esterifi cation activity about 6.73 U/g and 298.07 U/g, respectively. Lipase from rice bran had the hydrolitic and esterifi cation activity about 10.57 U/g and 324.03 U/g, respectively. The optimum conditions of esterifi cation reaction using germinated jatropha seed lipase as biocatalyst were crude enzyme concentration of 0.31 g/ml, molar ratio of oleic acid to ethanol of 1 : 1.81, and reaction time of 50.9 min. The optimum conditions of esterifi cation reaction using rice bran lipase were crude enzyme concentration of 0.29 g/ml, molar ratio of oleic acid to ethanol of 1 : 2.05, and reaction time of 58.61 min. The obtained amounts of OAEE were 810.77 μmole and 626.92 μmole for lipases from rice bran and germinated jatropha seed, respectively.